Strengthening Community Healthcare Administration Through Evidence-Based Nursing Practice: Empowering Interprofessional Nursing Policy - Chairun Nasirin; Arizky Farinsyah Pratama; Akbar Dwifarin Nugraha (LPPM STIKES Mataram, 2026)
Background: This study aimed to refine nursing policies by examining the effects of evidence-based guidelines on health and economic stability in economically disadvantaged Indonesian communities. The study was conducted in impoverished regions around Mataram in the West Nusa Tenggara Province of Indonesia. Methods: A qualitative case study approach was used to collect data from 34 individuals, including nurses, community health workers, local policymakers, community members, and midwives, through interviews and group discussions. Ethical approval for this study was obtained from the Institutional Review Board. Data analysis involved thematic coding of service delivery, health behavior, and policy engagement in NVivo 14. Results: This study highlighted significant health challenges among adolescents, including insufficient maternal health evaluations, inadequate screening for chronic diseases, and sanitation issues. Weak policies and limited community participation have exacerbated these issues. Conversely, areas with robust local policies exhibited improved health-seeking behavior and increased health awareness. These findings underscore the vital role of evidence-based approaches in nursing policies for promoting health equity and improving outcomes for underserved populations. Conclusion: Enhancing nursing policies requires adopting proven strategies to ensure equitable access to healthcare. This approach clarifies the benefits and challenges associated with accessing healthcare services.